Compound Verbs and Modalities of Process in Yulu (Central Sudanic) - (:unkn) unknown (My University, 2007)
Compound verbs are quite frequent in Yulu discourse (a Bongo-Bagirmi language of the Central African Republic and the Sudan) : two, three or even four verbs may be bound together to express what appears to be different parts of a same and single verbal process. Whereas some constituents of such compounds behave as fully free combined verbs, other ones are quite frequent and even specialized in this peculiar kind of context. Thus there is a set of about forty « postverbs » which usually appear in final position, and express values which have chiefly to do with – orientation/motion (« come », « go », « enter », « cross »...) – aspect/duration/‘aktionsart' (« do again », « do halfway », « get »...) – quality/quantity (« do well », « do a lot »...) All of them enable the speaker to be very precise and informative concerning several modalities of the verbal process in a very concise way. However the functional status of these « postverbs » is not unique in the sense that some of them go further along this trend to a more explicite grammatical nature. This peculiar evolution is twofold. In one case, « postverbs » lose their link to a verbal status and tend to handle like mere derivative morphemes. In the other case they tend to work as aspect markers, which as such can be combined with the whole range of verbs in the language. In both cases, although the formal nature of these elements still show a (compound) verbal origin, they definitely deserve a special treatment in a synchronic description.
Keywords: African Research